2002
DOI: 10.1080/10253890290027903
|View full text |Cite
|
Sign up to set email alerts
|

Postnatal Handling Induces Long-term Modifications in Central β-noradrenergic Signalling in Rats

Abstract: Neonatal handling has been shown to induce a short-term reduction in the binding properties of beta-adrenoceptors and in their primary biochemical responses in the young rat brain, which may account for the reduced responsiveness to stress observed in the handled rats. We have studied the persistence and duration of these changes in cerebral cortex, cerebellum and hippocampus at successive stages of life in neonatally handled rats. Binding properties of the beta-adrenoceptors in handled animals were essentiall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
0
3

Year Published

2006
2006
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 43 publications
1
7
0
3
Order By: Relevance
“…This effect is comparable to those previously reported in rats, where environmental stimulation produced long-lasting reduction of central noradrenergic responsiveness [67], and postnatal handling induced short- and long-lasting depression of AC functioning [42,43]. This may be explained since EE, when provided early in the life of normal animals, may also serve as a factor capable of moderating stressing responses, thus enabling the animals to cope more properly with learning challenges.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…This effect is comparable to those previously reported in rats, where environmental stimulation produced long-lasting reduction of central noradrenergic responsiveness [67], and postnatal handling induced short- and long-lasting depression of AC functioning [42,43]. This may be explained since EE, when provided early in the life of normal animals, may also serve as a factor capable of moderating stressing responses, thus enabling the animals to cope more properly with learning challenges.…”
Section: Discussionsupporting
confidence: 87%
“…Our previous work suggested that the long-lasting adaptation of the AC transduction system was a key element in the effects of neonatal handling in rats [42,43,44], and clear alterations of AC and PLC signaling systems in DS brains. We here aimed to assess the possible changes in G protein signaling systems upon postweaning EE in Ts65Dn mice.…”
Section: Introductionmentioning
confidence: 99%
“…Elevated NA activity enhances anxiety-like behavioral responses and inappropriate activation of the locus coreuleus (LC), may participate in the exaggerated stimulus-responsiveness and increased emotionality seen in patients with stress or anxiety disorders (Priolo et al, 1991;Aston-Jones et al, 1996;Goddard and Charney, 1997). On the other hand, antidepressant treatment, that is effective in panic disorder patients, decreases LC firing and tyrosine hydroxylase (TH, rate-limiting enzyme in the synthesis of catecholamines) expression (Smith et al, 1995), and behavioral manipulations that decrease stress, such as postnatal handling modulate the responses of the noradrenergic system (Escorihuela et al, 1995a,b;Baamonde et al, 1999Baamonde et al, , 2002.…”
mentioning
confidence: 99%
“…Knowing that quinpirole, a selective dopamine D2/D3 receptor agonist, decreases the preference for chocolate biscuits consumption in rats (Cooper & Al-Naser, 2006), it is possible that imipramine's action increasing D3 receptor expression in the nucleus accumbens of neonatally handled rats would therefore inhibit their natural preference for palatable food. Norepinephrine also plays an important role in the regulation of hunger and satiety (Wellman, 2000), and it is described that handling during early postnatal life influences central noradrenergic transmission (Baamonde et al, 1999(Baamonde et al, , 2002. While associated with sucrose sham-feeding (Hajnal & Norgren, 2004) and palatable food consumption (Fallon et al, 2007), the total amount of norepinephrine in the nucleus accumbens was measured in another study from our group (Silveira et al, 2009) and it was not different between neonatally handled and nonhandled animals in adulthood.…”
Section: Discussionmentioning
confidence: 77%